-13=n+36-

Simple and best practice solution for -13=n+36- equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13=n+36- equation:


-13=n+36-

We simplify the equation to the form, which is simple to understand
-13=n+36-

We move all terms containing n to the left and all other terms to the right.
-1n=+36-0+13

We simplify left and right side of the equation.
-1n=+49

We divide both sides of the equation by -01 to get n.
n=-49

See similar equations:

| 2x^2-4x+16=0 | | b-56=3148 | | 25+15w=235 | | X-(4x-7)=.5x-(x+21) | | K-16=k-24 | | 5f-8=2f+1 | | 2x+y=79-x | | 19+7y=10y-17 | | 7(x+3)-2(x+4)=28 | | v^2-9v+14= | | 3x^3-x^2y+12x-4y=0 | | 2n-(4n+5)=-6(n-3)-1 | | 4x^2-7x+9=5x+4 | | 13-4f=16 | | -2(-6x+9)=36 | | 2x^4y-3x^3y+20x=0 | | -4x+10=-6x-2 | | 9x+5=6x+41 | | -2(-6+9)=36 | | 8e-12=3e-2 | | -3x+27=12 | | 13=n+36 | | 3(5x-1)=3x-15 | | 2x+6=5+2x | | -3x-16=2x-21 | | 9x^3y+33x^2y^2+30xy^3=0 | | 14-4n=n-3n | | 5(c-4)=2(c+5) | | 11-1=4x-7x+x | | -36=4(x+1) | | -9x+18=-6x+27 | | x+e=1 |

Equations solver categories